Caspase-8 Promotes Pulmonary Hypertension by Activating Macrophage-Associated Inflammation and IL-1β (Interleukin 1β) Production. Issue 5 (7th April 2022) - Rong, Wuwei; Liu, Chenchen; Li, Xiaoming; Wan, Naifu; Wei, Lijiang; Zhu, Wentong; Bai, Peiyuan; Li, Ming; Ou, Yangjing; Li, Fang; Wang, Lingxia; Wu, Xuanhui; et al.
Abstract : Background: Macrophages are involved in the pathogenesis of pulmonary arterial hypertension (PAH). Caspase-8, an apical component of cell death pathways, is significantly upregulated in macrophages of PAH animal models. However, its role in PAH remains unclear. Caspase-8 plays a critical role in regulating inflammatory responses via inflammasome activation, cell death, and cytokine induction. This study investigated the mechanism of regulation of IL-1β (interleukin 1β) activation in macrophages by caspase-8. Methods: A hypoxia + SU5416-induced PAH mouse model and monocrotaline-induced rat model of PAH were constructed and the role of caspase-8 was analyzed. Results: Caspase-8 and cleaved-caspase-8 were significantly upregulated in the lung tissues of SU5416 and hypoxia-treated PAH mice and monocrotaline-treated rats. Pharmacological inhibition of caspase-8 alleviated PAH compared with wild-type mice, observed as a significant reduction in right ventricular systolic pressure, ratio of right ventricular wall to left ventricular wall plus ventricular septum, pulmonary vascular media thickness, and pulmonary vascular muscularization; caspase-8 ablated mice also showed significant remission. Mechanistically, increased proliferation of pulmonary arterial smooth muscle cellss is closely associated with activation of the NLRP3 (NOD [nucleotide oligomerization domain]-, LRR [leucine-rich repeat]-, and PYD [pyrin domain]-containing protein 3) inflammasome and the IL-1β signaling pathway. Although caspase-8 did not affect extracellular matrix synthesis, it promoted inflammatory cell infiltration and pulmonary arterial smooth muscle cell proliferation via NLRP3/IL-1β activation during the development stage of PAH. Conclusions: Taken together, our study suggests that macrophage-derived IL-1β via caspase-8-dependent canonical inflammasome is required for macrophages to play a pathogenic role in pulmonary perivascular inflammation.